Numerical analyses on performance of low carbon containership - Li Chin Law; Mohd Roslee Othman; Epaminondas Mastorakos (Energy Reports, 2023)
Onboard Carbon Capture and Storage (OCCS) was found to be a potential approach for maritime decarbonization. By using the optimized OCCS, 90% carbon capture rate was achieved with a lower regeneration duty of 3,637 MJ/ton CO2. It was also found that with integration of waste heat recovery (WHR), the regeneration duty of CCS can be further reduced by 58.5% to 1,510 MJ/ton CO2. Detailed numerical analyses on CCS-Ship showed that the OCCS installation onboard of the reference ship used less than 15% of the total ship length. In contrast, the E-Ship would occupy 80% of deck area for battery installation. In addition, the CSS-Ship was found to retain 97.73% of cargo, consume 66.94 kJ/ton.nm of ES, incur $0.00093/ton.nm of CS, and improve the attained EEDI to 0.49 gCO 2/ton.nm, which improved the ship EEDI by 88% as compared to the ship built in year 2000-2010. Numerical analyses between various alternative fuelled-ships showed that the ship with CCS installation (CCS-Ship) was at least 1 time and 12 times more economical than hydrogen fuelled-ship (H2-Ship) and electrically propelled-ship (E-Ship) respectively. The data obtained from this research suggest that OCCS is a promising decarbonization alternative for shipping industry with relatively low cost, less than 3% capacity loss and that it achieved 88% of EEDI improvement.